In Vivo Modeling of Tumor Heterogeneity for Immuno‐Oncology Studies: Failures, Improvements, and Hopes. Issue 3 (7th March 2022) - DiMarco, Ashley V.; Maddalo, Danilo
Abstract: Murine tumor modeling is fundamental for the preclinical development of anti‐cancer therapies. Use of immunocompetent mouse models is becoming increasingly relevant as we gain more knowledge of how cancer cells interact with the immune system in the tumor microenvironment and how we can harness the immune system to fight tumors. However, there are few intrinsically immunogenic preclinical tumor models, and the vast majority either do not respond to therapy or do not faithfully predict the responses of the therapy when applied in the clinic. Here, we discuss the limitations of commonly used murine tumor models in immuno‐oncology and strategies to improve their immunogenicity and mutational burden to more accurately reflect the heterogeneity of patient tumors. © 2022 Wiley Periodicals LLC.